Application of Multiple-Criteria Decision-Making Technology in Emergency Decision-Making: Uncertainty, Heterogeneity, Dynamicity, and Interaction - Tao Li; Jiayi Sun; Liguo Fei (Mathematics)
With the increasing frequency of natural and man-made disasters, emergency management has become a key research field aimed at saving lives and reducing environmental and economic losses. As the core link in responding to sudden crisis events, emergency decision-making is directly related to the stability of society, the safety of citizens, and the robustness of infrastructure. As a scientific method, multiple-criteria decision-making (MCDM) technology has gradually become an important tool for solving complex decision-making problems in emergency management. It can handle the uncertainty, heterogeneity, dynamicity, and interaction in emergencies and select the best alternative or rank all options for multiple reference attributes in a limited number of options to solve decision-making problems. This paper comprehensively reviews the existing relevant literature, analyzes the current status and challenges of MCDM technology in its application process and in emergency management, and proposes research gaps and development directions in this field.